Contraceptive subcutaneous device migration: what does an orthopaedic surgeon need to know? A case report and literature review. - Rivera, Fabrizio; Bianciotto, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Subdermal contraceptive implant is approved in more than 60 countries and used by millions ofwomen around the world. Although relatively safe in nature, their implantation and removal may be associatedwith potential complications, some of which may require surgical intervention. Two types of peripheralneurological complications are reported: complications related to compressive neuropathy caused by devicedecubitus and complications related to device improper removal. An healthy 35-year-old woman come to ourattention for paresthesia from medial side of right elbow to fourth and fifth fingers. Tinel sign was positiveon medial side of distal third of right arm, above the elbow, as well. Clinical history of patients revealed asubcutaneous placement of a etonogestrel implant 3 years before. Patients reported disappearing of tactile feeling of subcutaneous contraceptive implant since two months. At clinical examination, implant was not felt in its original subcutaneous place. X-rays control revealed its proximal and deep migration. Surgical exploration for subcutaneous contraceptive implant removal revealed it lying on the ulnar nerve. Patient referred immediate paresthesia disappearing after surgery. At 1 month follow up no motor or sensory alteration were evident. Removal of implants inserted too deeply must be carefully performed to prevent damages to nervous and vascular structures and it should be performed by operators who are very familiar with the anatomy of the arm. In case of chronic neuropathy caused by implant nerve compression only an appropriate patients information about rare but possible neuropathic symptoms related to device migration and a careful medical history collecting can avoid a mistaken diagnosis of canalicular syndrome.